Marriage And Financial Greed In Post Independent Africa: A Review Of Xala And Le Témoin - Rabiu Iyanda (The Journal of Studies in Language, Culture and Society)
Literature is the projection of the society where such emanates. Marriage, the union of two people drawn together by love and a dynamic aspect in the life of human beings continues to be field interest to scholars across several fields of studies: sociologists, religionists, philosopher literary writers view polygamy and its effects adored by Africans and Muslims differently. Before the advent of foreign cultures and religions in Africa, this type of marriage is much cherished and worth of any man is measured by the numbers of wives under his roof. This paper investigates societal views on the marital choices using practice literary theory. It demonstrates how Sembène in Xala, (Francophone West Africa, Senegalese and Ajiboye in Le Témoin Anglophone West Africa, Nigeria present respectively marriage in their individual milieu. How these writers use their texts to divulge reasons, and effects of polygamy on its practitioners in their respective societies. The changes brought about by the modern life industry and cities to African marriages and to the roles of men and women in a matrimonial setting is also x-rayed. The paper reveals some reasons for being polygamous such as personal motives, economy, prestige and competition for power. The consequences of polygamy on the society, both traditional and modern, and some plausible ways to curtail the negative effects in the contemporary days are proffered. Keywords: culture, literature, marriage, practice literary theory.